Penerapan Manajemen Stress Non Farmakologis Pada Ibu Hamil Di Bpm Febra Ayudiah, SST, M.H - Lugita, Liya; Sulastri, Mepi; Iswari, Indra (Universitas Dehasen Bengkulu, 2024)
Stress in pregnancy has the potential to cause morbidity during pregnancy. Complications that arise due to prenatal stress include: preterm labor caused by the placenta increasing the production of corticotropin-releasing hormone (CRH) and progesterone in stressful situations. Apart from that, at the beginning of pregnancy stress and a decrease in progesterone can cause abortion, progesterone which is calming and slows down gastric motility can trigger hyperemesis gravidarum and low birth weight (LBW) babies. This impact proves that the mother's mental state can influence the mother's health during pregnancy and the baby's growth and development in the next period of life (King et al, 2010; Woods et al, 2010; Silviera et al, 2012). Therefore, it is necessary to educate pregnant women about how to manage stress well with a stress management approach..So the aim of this activity is to improve health and reduce stress and be able to manage your own stress in pregnant women. After providing material and training to pregnant women at BPM Febra Ayudiah, SST, M.H, it was found that there was an increase in knowledge and pregnant women were able to reduce their stress by using the deep breathing relaxation technique, which is a non-pharmacological method for reducing stress.